2001
DOI: 10.1046/j.1440-1746.2001.02630.x
|View full text |Cite
|
Sign up to set email alerts
|

Extending the reading time increases the accuracy of rapid whole blood test for diagnosis of Helicobacter pylori infection

Abstract: The BM-Test is an appropriate office-based test for diagnosing H. pylori infection in Chinese patients. Extending the reading time would facilitate the readability of rapid blood tests with a resultant increase in accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…There were several studies demonstrating that the sensitivity of serological diagnosis of H. pylori infection was higher in the older group (Ն45 years) than in the younger group (Ͻ45 years) (2,7,20). Our study showing higher antibody levels in the older group in H. pylori-infected patients could explain this phenomenon, because the higher the antibody levels, the fewer false negatives there will be.…”
Section: Discussionmentioning
confidence: 43%
“…There were several studies demonstrating that the sensitivity of serological diagnosis of H. pylori infection was higher in the older group (Ն45 years) than in the younger group (Ͻ45 years) (2,7,20). Our study showing higher antibody levels in the older group in H. pylori-infected patients could explain this phenomenon, because the higher the antibody levels, the fewer false negatives there will be.…”
Section: Discussionmentioning
confidence: 43%
“…Qualitative rapid antibody tests have in general been clearly inferior to the quantitative enzyme immunoassay based serological tests and thus, the use of rapid tests has not been recommended [1]. The weak performance of rapid tests was further supported in a recent study [52], although somewhat better results were also reported [53,54].…”
Section: Serological Testsmentioning
confidence: 99%
“…A further study of two rapid whole blood tests (BM Test Helicobacter pylori and QuickPacIVOne Step H. pylori Whole Blood Test) in a Chinese population compared to a conventional ELISA (HEL‐p TEST II) in 141 patients, showed a sensitivity and specificity of 94.4% and 94.1% at 360 min and 74.2% and 96.1% at 10 min for the BM Test; 80.9% and 76.5% at 395 min and 3.4% and 100% at 10 min for the QuickPakIVtest. When the length of incubation of the test are increased beyond the manufacturers recommended time the BM test particularly seems to be a good screening test 19 …”
Section: Assessment Of Near‐patient Testsmentioning
confidence: 99%